2015
DOI: 10.1038/srep16630
|View full text |Cite
|
Sign up to set email alerts
|

The coastal ocean response to the global warming acceleration and hiatus

Abstract: Coastlines are fundamental to humans for habitation, commerce, and natural resources. Many coastal ecosystem disasters, caused by extreme sea surface temperature (SST), were reported when the global climate shifted from global warming to global surface warming hiatus after 1998. The task of understanding the coastal SST variations within the global context is an urgent matter. Our study on the global coastal SST from 1982 to 2013 revealed a significant cooling trend in the low and mid latitudes (31.4% of the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 42 publications
(79 reference statements)
4
47
2
Order By: Relevance
“…This data set has been widely used in scientific researches [16][17][18][19]. The suitability of the data base to identify extreme events was previously shown in work of Lima and Wethdy and Liao et al [16,20].…”
Section: Data Sourcementioning
confidence: 96%
“…This data set has been widely used in scientific researches [16][17][18][19]. The suitability of the data base to identify extreme events was previously shown in work of Lima and Wethdy and Liao et al [16,20].…”
Section: Data Sourcementioning
confidence: 96%
“…Being jointly determined by coastal topography and sea level, the area of each land section has an innate temporal auto-correlation, which should be considered to the estimation of coastline change rate. Thus, for each land section, the freedom degree was computed using the Quenouille procedure [62]. The standard deviation was calculated using the resulting freedom value for assessing the uncertainty.…”
Section: Uncertainty Assessmentmentioning
confidence: 99%
“…Moreover, Xie et al () found that the annual mean temperature in China exhibited a cooling trend during the recent global warming hiatus period, suggestive of a robust warming hiatus in China. Liao et al () studied the coastal ocean response to the global warming acceleration and hiatus and found a significant cooling trend in the low latitudes and midlatitudes (i.e., 31.4% of global coastlines) after 1998, including China's offshore waters. Our results are consistent with those of previous studies.…”
Section: Resultsmentioning
confidence: 96%